2014
DOI: 10.1103/physrevlett.112.166102
|View full text |Cite
|
Sign up to set email alerts
|

CO Tip Functionalization Inverts Atomic Force Microscopy Contrast via Short-Range Electrostatic Forces

Abstract: We investigate insulating Cu 2 N islands grown on Cu(100) by means of combined scanning tunneling microscopy and atomic force microscopy with two vastly different tips: a bare metal tip and a CO-terminated tip. We use scanning tunneling microscopy data as proposed by Choi, Ruggiero, and Gupta to unambiguously identify atomic positions. Atomic force microscopy images taken with the two different tips show an inverted contrast over Cu 2 N. The observed force contrast can be explained with an electrostatic model,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 35 publications
8
84
0
Order By: Relevance
“…Here the hollow sites show the darkest contrast whereas the brightest spots occur above the nitrogen atoms. These images match previous experimental findings on Cu 2 N with Cu-and Co-terminated tips 19 . To examine the contrast mapping more closely, we plotted the vertical force on each tip as a function of tip height over the different sites (Fig.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Here the hollow sites show the darkest contrast whereas the brightest spots occur above the nitrogen atoms. These images match previous experimental findings on Cu 2 N with Cu-and Co-terminated tips 19 . To examine the contrast mapping more closely, we plotted the vertical force on each tip as a function of tip height over the different sites (Fig.…”
supporting
confidence: 91%
“…A previous study has reported that long-range electrostatic forces can also influence contrast inversion 19 . We find that at very large tip distances for the CO tip (z = 6.88Å for Cu 2 N and z = 5.21Å for graphene), AFM images are inverted compared to those at intermediate distances (z ∼ 3.39Å).…”
mentioning
confidence: 97%
“…1(e)]. The metallic tip apex atom has a dipole moment induced by the Smoluchowski effect [25], whose direction is the same as that of the CO molecule adsorbed on the surface [26]. Thus in the distance regime where the electrostatic interaction between the tip and the molecule dominates, the force between them is attractive.…”
mentioning
confidence: 99%
“…Here z is the tip-sample distance, and p is the dipole of the tip, estimated to be 0.5 D [23] or 0.9 D [24] for copper tips [25]. The corresponding frequency shift…”
Section: (B) Ifmentioning
confidence: 99%
“…2(a), we need to set the zero of the z axis; that is, we need to estimate the position of the surface. To this end, we employed a commonly used approximation assuming z = 0 at the "point contact", where the tunneling conductance would reach G 0 = 2e 2 /h ≈ 77.5 μS with a nonoscillating sensor [24,27].…”
Section: (B) Ifmentioning
confidence: 99%